2022
DOI: 10.1007/s11764-022-01294-w
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 pandemic has affected eating habits and physical activity in breast cancer survivors: the DianaWeb study

Abstract: Purpose Breast cancer (BC) survivors are increasingly interested in learning about healthy lifestyles to reduce the risk of BC recurrence and mortality. The DianaWeb study, a community-based participatory research, offers BC patients a specific interactive website to help them in adopting and maintain correct lifestyles, in line with World Cancer Research Fund recommendations. However, to limit the spread of the COVID-19 pandemic, most countries introduced restrictions which, inevitably, caused s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…[ 68 ] For instance, studies examining children [ 69 ] and adults [ 70 ] reported that there was a recovery in PA levels of children and adults after the lockdown was released; however, this level could not reach the same level before the pandemic. Other topics that attracted the interest of researchers were the way COVID-19 affected PA habits [ 71 , 72 ] and the relationship between COVID-19 based anxiety and sleeping pattern [ 73 , 74 ] and the sample consisted of individuals in childhood period. These studies inquired about how COVID-19 affected PA levels of children, if the PA level of children changed due to the release of lockdown and PA habits and needs of children.…”
Section: Discussionmentioning
confidence: 99%
“…[ 68 ] For instance, studies examining children [ 69 ] and adults [ 70 ] reported that there was a recovery in PA levels of children and adults after the lockdown was released; however, this level could not reach the same level before the pandemic. Other topics that attracted the interest of researchers were the way COVID-19 affected PA habits [ 71 , 72 ] and the relationship between COVID-19 based anxiety and sleeping pattern [ 73 , 74 ] and the sample consisted of individuals in childhood period. These studies inquired about how COVID-19 affected PA levels of children, if the PA level of children changed due to the release of lockdown and PA habits and needs of children.…”
Section: Discussionmentioning
confidence: 99%